Evaluation of the Dietary Black Soldier Fly Larvae Meal (Hermetia illucens) on Growth Performance, Intestinal Health, and Disease Resistance to Vibrio parahaemolyticus of the Pacific White Shrimp (Litopenaeus vannamei) - Chen, Yongkang; Chi, Shuyan; Zhang, Shuang; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Tan, Beiping; Xie, Shiwei (Frontiers in Marine Science, 2021)
The present study evaluated the effects of dietary black soldier fly larvae meal (BSF) on growth, intestinal health and susceptibility to Vibrio parahaemolyticus in Pacific white shrimp Litopenaeus vannamei. The basal diet was formulated to contain 25% fish meal, and then 10%, 20% and 30% of the fish meal protein were replaced by BSF in the experimental diets, which referred to FM, BSF10, BSF20 and BSF30, respectively. 480 shrimp (0.88 ± 0.00g) were equally distributed to four groups of three replicates, each replicate in a 300L tank with 40 shrimp and fed four times daily for 7 weeks. Results showed that growth performance did not change significantly in shrimp fed BSF10 and BSF20 diets, but significantly decreased in those fed BSF30 diet compared to FM. After feeding trial and sampling, a Vibrio parahaemolyticus infection challenge trial was conducted, showing that the survival rate of shrimp fed BSF10 significantly higher than those fed FM. Results of midgut histology showed that the width and height of intestinal mucosal folds decreased significantly in shrimp fed BSF20 and BSF30, and the early signs of apoptosis in the intestinal cells were found in shrimp fed BSF30. The mRNA levels of non-specific immune-related genes dorsal and relish were downregulated in shrimp fed BSF20 and BSF30 diets. The mRNA levels of antimicrobial peptides-related genes alf (anti-lipopolysaccharide factor) were upregulated in shrimp fed BSF10 but downregulated in shrimp fed BSF30. The mRNA level pen3 (penaeidins 3) was upregulated in shrimp fed BSF10 and BSF20 diets. The intestinal bacterial communities on OTU levels among groups were not significantly differentiated according to the beta diversity analysis. At the genus levels, a decrease in Vibrio, Photobacterium and Candidatus_Bacilloplasma, as well as the increase in Bacillus and Pseudoalteromonas abundance, indicated the improvement of intestinal microbiota in shrimp fed dietary BSF. Therefore, the use of BSF in shrimp diet should be controlled at a dosage of 20% of the fish meal, which can improve the intestinal microbiota without causing negative effects.